The great gelatin revival : savory aspics, jiggly shots, and outrageous desserts - Albala, Ken, 1964- (University of Illinois Press, 2023)
"Once synonymous with food novelty, gelatin has re-emerged as an attention-grabbing element of creative cuisine and avant-garde drinkology. Ken Albala's most fearless food exploration yet takes readers into the sublime world of aspics past and present. Blending history with his trademark zeal for experimentation, Albala traces gelatin's ever-changing fortunes alongside one-of-a-kind recipes that inspire, delight, and terrify as only jello can do. Gelatin's wondrous arrival in the medieval era was part of a technological watershed. Today, it reflects our high-tech zeitgeist. Albala encourages readers to celebrate gelatin's return with advice on creating a base and making silicone molds while his outrageous original creations dare you to add some jiggle to breakfast (Eggs Benedict in Champagne Jello), a nightcap (Froot Loop Negroni), or any culinary moment in between. A lighthearted manifesto for the new age of aspics, The Great Gelatin Revival rattles our very understanding of what food can be"--